Development of Genistein-Loaded Nanogel for Skin Aging: An in vitro and in vivo Study - Harwansh, Ranjit Kumar; Rahman, Mohammad Akhlaquer; Deshmukh, Rohitas (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Generating Reactive Oxygen Species (ROS) at high altitudes causes several disorders, including skin aging. Genistein (GN) is a potent herbal bioactive compound found in many herbs like Soy GN has been reported to have several beneficial health effects, including antioxidant and photoprotection activities. However, their therapeutic efficacy is limited because of low solubility and poor oral bioavailability. Objectives: The current work was designed to formulate a nanoemulsion of GN in nanogel to ensure its enhanced bioavailability and improved UVA protection effect against oxidative stress. Results: The best formulation, GN-NE2, was composed of oil-labrafac Lipophile WL1349, water and Smix (surfactant-labrasol and cosurfactant-PEG 400) at an optimized ratio (15:30:55% w/w), respectively. Ex vivo skin permeation, in vivo bioavailability and in vivo UVA protection activity of GN-NE2-based nanogel (GN-NG2) were studied using a rat skin model. GN-NG2 exhibited a sustained release profile as compared to its conventional gel. Moreover, significant skin permeability (p<0.05) and enhanced photo-protection potential were achieved with GN-nano gel when compared with conventional gel. Conclusion: GN-NG2 exhibited improved UVA protection efficacy and antioxidant effect because of enhanced trans-cutaneous absorption. Thus, nanogel could be a promising approach to combat UVA-mediated skin damage.
Keywords: Nanogel; Oxidative stress; Bioavailability; UV rays; Genistein; Nanoemulsion